Chronic Cavitary Pulmonary Aspergillosis: Complication of Pulmonary Tuberculosis - Tiwari, Bishal; Adhikari, Sudeep; Ghimire, Manoj; Singh, Suraj; Kafle, Amir (Journal of Nepal Health Research Council, 2024)
Pulmonary Aspergillosis is a fungal infection of the lungs that can lead to invasive disease and the formation of cavities, especially in the immunocompromised population. The most common clinical features are no symptoms at all to fever, cough, nondescript chest discomfort, trivial hemoptysis, and shortness of breath. Most patients respond well to Itraconazole therapy. Pulmonary Tuberculosis is one of the conditions that can lead to Aspergillosis, especially in cavities that are formed by Mycobacteria; both often manifest with similar clinical features and lead to diagnostic error. We present a case of a 28-year-old male diagnosed with pulmonary tuberculosis who developed symptoms of persistent cough, hemoptysis, increasing fatigue, and weight loss despite compliance with antitubercular therapy. Ultimately diagnosis of Cavitary pulmonary aspergillosis was made on clinical, laboratory, and radiological grounds. In a patient presenting with worsening symptoms of tuberculosis, there should be a suspicion of aspergillosis, necessitating the performance of standard fungal infection investigations. Keywords: Immunocompromise iosts; lung cavity; pulmonary aspergillosis; tuberculosis.